(untitled) (Washington, 1990)
Will Japan's economic structure change? confessions of a former optimist; The U. S. - Japan trade problem an economic analysis from a Japanese viewpoint; Trade, revisionism and the rule of law the nature of the trade conflict and the American reponse,....
Keywords: Nhật Bản,Japan; Chính sách kinh tế,Economic policy; 1945 -,1945-